Study of the loss of microwave signal in sand and dust storms - Srivastava S.K.; Vishwakarma B.R. (My University, 2025)
A theoretical investigation was conducted to examine the propagation characteristics of millimeter waves in sand and dust storms. The storm is considered to have three main constitutes i.e. sand, silt and clay. Reflection coefficients, transmission coefficients and absorption loss were calculated using derived equations. The propagation parameters are found to depend both on frequency and visibility. It has been found that for sparsely distributed particles the reflection coefficient is reduced by several orders of magnitude as compared to the case of zero visibility. The calculated values of propagation parameter in this analysis are compared with earlier reported value of transmission line model. This verifies the accuracy of theory developed.